2023
DOI: 10.48048/tis.2023.4690
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Fluoride from Aqueous Solution using Eggshell Pretreated with Plasma Technology

Abstract: Fluoride is a toxic substance that can cause adverse effects on human health such as dental and skeletal fluorosis. Therefore, the objective of this study was to investigate the adsorption potential of fluoride from aqueous solution using eggshell pretreated with plasma technology and compare to untreated eggshell. The batch adsorption experiments of fluoride from aqueous solution using pretreated eggshell and untreated eggshell were carried out to compare their performances on fluoride removal efficiency, ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The authors reported batch experiments and observed than the weak acidic pH favored the fluoride adsorption. Khiewwijit et al [50] investigated the adsorption of fluoride from an aqueous solution using eggshell pretreated with plasma technology and compared to untreated eggshell. The maximum fluoride removal efficiency increased from 59.88% with untreated eggshell to 90.34%, which was due to an increase in adsorption sites after the surface modification process of the eggshell.…”
Section: Adsorption Process For Defluoridation: General Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported batch experiments and observed than the weak acidic pH favored the fluoride adsorption. Khiewwijit et al [50] investigated the adsorption of fluoride from an aqueous solution using eggshell pretreated with plasma technology and compared to untreated eggshell. The maximum fluoride removal efficiency increased from 59.88% with untreated eggshell to 90.34%, which was due to an increase in adsorption sites after the surface modification process of the eggshell.…”
Section: Adsorption Process For Defluoridation: General Principlesmentioning
confidence: 99%
“…Balancing process effectiveness against the associated costs of increasing the amount of adsorbent is essential and requires meticulous evaluation. Several studies by Wang et al [50], Sapna et al [52], Li et al [78], Grace Lee et al [76], Lee et al [80], and Yu et al [79] have explored diverse adsorbents, presenting promising results in terms of adsorption capacity. Collectively, these studies offer insights into the potential effectiveness of various adsorbents for fluoride removal, contributing to ongoing efforts to optimize engineering solutions for water treatment processes.…”
Section: Fluoride Adsorption Capacity and Engineering Implicationsmentioning
confidence: 99%